1972
DOI: 10.1021/bi00760a038
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and conformational stability of ribonuclease A and its peptic derivative, des-(121-124)-ribonuclease

Abstract: We have determined the near-ultraviolet circular dichroic spectrum (235-315 nm) and the ultraviolet difference absorption spectrum of ribonuclease A (RNase A) and its peptic derivative, des-(121-124)-RNase A (RNase P), which is missing the four C-terminal residues and retains no more than a few per cent of the enzymic activity of RNase A. The circular dichroic spectra of both proteins were resolved into gaussian parameters and the rotational strengths of the resolved bands (due mainly to tyrosines and disulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 75 publications
5
27
0
Order By: Relevance
“…All samples were dissolved in 100 mM sodium phosphate buffer, pH 6.55. The reduced mean residue ellipticities ([ θ ] res ) were calculated taking in account that the mean residue molecular weight for pancreatic RNase A is 110.5 [17].…”
Section: Methodsmentioning
confidence: 99%
“…All samples were dissolved in 100 mM sodium phosphate buffer, pH 6.55. The reduced mean residue ellipticities ([ θ ] res ) were calculated taking in account that the mean residue molecular weight for pancreatic RNase A is 110.5 [17].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the positive maximum at 231 nm in AA has been assigned t o tyrosine residues (Kay, 1976). Similar assignments to tyrosine residues have been made for the 232nm band of human carbonic anhydrase B , the 234 nm bands of the 1.9 S soybean inhibitor and lima bean inhibitor , the 230nm band of ribonuclease A (Sinions & Blout, 1968;Pflum & Beychok, 1969;Puett, 1972). the 233nm band of the a-subunit of oLH (Bewley et a l , 1972a;Holladay & Puett, 1975), and the 228 nm band of cobrotoxin (Chen et al, 1977).…”
Section: Below 225nmmentioning
confidence: 64%
“…The 232.5 positive CD extremum observed in ovine lutropin-a is reminiscent of a similar band in bovine pancreatic ribonuclease (Puett, 1972) and mouse submaxillary epidermal growth factor (Holladay et ul., 1976). Previously, we suggested that tyrosines 21 and 30 in ovine lutropin-a contribute significantly to this band.…”
Section: Peraturesmentioning
confidence: 88%